Analisis Komparatif Kalsium, Zat Besi, dan Proksimat Bubuk Ikan Berbasis Gabus (Channa striata) dan Hasil Sampingnya - Puteri, Nafisah Eka; Jameelah, Maryam; Giovani, Sarah; Ichsan, Vicky Permatasari Almira (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Snakehead (Channa striata) is a widely fish commodity in Indonesia. This research was conducted to develop fish powder product, that was rich in energy and high-quality micronutrients. This research also aims to observe the nutritional value of fish powder derived from snakehead and its by-products, in order to fulfill nutritional value of food products. The results showed that the bone (BN) was smallest reduction in mass compared to the meat (MT), head (HD), and skin (SK) (p<0.05). The fat content of bone-based fish powder was found to be similar to that of the meat part, and even higher than other parts. The highest calcium and iron content (72108.13 mg/kg) was found in bone-derived fish powder, followed by head-based powder (58295.67 mg/kg) and skin-based powder (34782.12 mg/kg) of snakehead. The lowest iron content was observed in meat-based powder (33.44 mg/kg). However, the iron levels in fish powder made from head, skin, and bones were not significantly different, measuring 67.52 mg/kg, 87.27 mg/kg, and 68.99 mg/kg, respectively. Therefore, the result will be helpful for developing snakehead powder as commercial product.